A comprehensive review on past, present and future aspects of canine theileriosis. (January 2019) - Nayyar Ghauri, Hammad; Ijaz, Muhammad; Farooqi, Shahid Hussain; Ali, Ahmad; Ghaffar, Awais; Saleem, Sehrish; Iqbal, Muhammad Kashif; Aziz, Muhammad Umair; Ghani, Usman; Ullah, Muhammad Rafi; Ahmad, Hafiz Manzoor
Abstract: Canine theileriosis is a notorious tick borne piroplasmid infection of wild and domestic canines. The causative agent has not yet been accurately classified. PCR studies revealed that causative agent resembles to Theileria genus and thus provisionally named as Theileria annae . The other Theileria species reported in canines is Theileria annulata, Theileria equi and unnamed Theileria specie. This emergent canine infection is considered to be endemic in most of the European countries. However in Asia this disease has not been reported till date. The vectors responsible for transmission of this disease have not been determined. It has been suggested that DNA of Theileria annae has been detected in hard tick Ixodes hexagonus in Northwestern Spain and several other tick species. Clinically canine theileriosis is characterized by severe weakness, fever, hemoglobinuria and anemia. Recently atovaquone or buparvaquone plus azithromycin therapy showed better clinical efficacy. This comprehensive review is intended to summarize the current knowledge on prevalence and epidemiology of canine theileriosis in different countries of the world and associated tick vectors. Highlights: Canine theileriosis is a notorious tick borne piroplasmid infection. The infection is considered endemic in Europe but not studied to this extent in Asia. Responsible vectors for transmission of this disease have not been precisely determined. The clinical picture of disease is quite severe. Atovaquone or buparvaquone with azithromycin have shown clinical efficacy.